Susceptibility of different Malvaceae crops to herbivory induced by adult Podagrica spp. - Ekoja, Edache Ernest; Pitan, Olufemi Richard (Journal of Scientific Agriculture, 2022)
Podagrica uniforma Jacoby and P. sjostedti Jacoby are two important flea beetles that cause economic damage to several Malvaceae crops in Africa. Host preference by the beetles was evaluated under field conditions in 2017 and 2018 using fourty different crops in the family Malvaceae. The setup was a randomized complete block design with three blocks. Both P. uniforma and P. sjostedti highly preferred the okra genotypes, but the cotton genotypes were not damaged in both years. More than 80% of the crop leaves had beetle-induced buckshot(s) except for cotton (0%) and jute mallow (<55%). Leaf tissue removal exceeded 40% of the total leaf area of kenaf. Damages induced by the beetles disrupted plants’ fitness, caused high leaf abscission and many crop stands were lost in both years. Only the okra fruits were damaged by the beetles, and plots with the Dwarf LP variety of okra recorded the highest crop loss (>43%) in both years. NHAe47-4, LD-88, and Dwarf LP okra genotypes were the first three Malvaceae crops that were most susceptible to Podagrica spp. attacks, while cotton genotypes were ranked as the least preferred crops. In conclusion, P. uniforma and P. sjostedti exhibited broad oligophagy in a polyculture of Malvaceae crops. While okra, kenaf, roselle, and jute mallow showed varying degrees of susceptibility to the beetles’ attacks, the cotton genotypes appeared to be outside the host range. The potential of utilizing this beetle-Malvaceae interaction information in agroecosystems to minimize Podagrica spp. infestation and crop losses were discussed.